Efektivitas Pelaksanaan Program Asuransi Usaha Tani Padi (AUTP) di Kabupaten Tabanan - Sri Mastini, Luh Putu Widia; Susrusa, Ketut Budi; Budiasa, I Wayan (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 01 (2023): Jurnal Managemen Agribisnis, 2023)
The sector needs serious attention from the government through development programs and policies that are able to boost and real agriculture to national economic growth and ensure national food security in order to meet household consumption needs. One of them is agricultural insurance by involving farmers as partners and beneficiaries of the program. The purpose of this study was to determine farmers' perceptions of the AUTP program in Tabanan Regency, analyze the comparison of claim funds with production costs in Tabanan Regency and analyze the effectiveness of the AUTP program implementation in Tabanan Regency. This research was conducted in Tabanan Regency. The data analysis method used is descriptive analysis method and class interval for purposes one and three while cost analysis is for purposes two. The results showed (1) Tabanan Regency as a correspondent by looking at the perception or attitude which is a form of farmers' responses to the implementation of the program in general is in the effective category with an overall score management average of 82%. provide a good perception of the program with six indicators, namely farmer satisfaction with AUTP, commitment to AUTP farmers, premium payment in accordance with AUTP benefits, AUTP technical officer services, farmer awareness of the importance of AUTP and farmers' commitment to paying premiums. (2) Production costs incurred by farmers for one planting season for 1 (one) ha arable land are Rp 2.458.150 . When compared with the average claim for AUTP funds received by farmers of Rp. 2,580,000, the percentage of AUTP benefits is 105.0%. The result of the comparison of production costs and AUTP claims is that there is an excess of Rp. 121.850 (105,0% of the claims obtained). (3) The effectiveness of the implementation of the AUTP program in Tabanan Regency in the implementation of the rice farming insurance program has achieved the goal of protecting farmers from the risk of crop failure caused by natural disasters, extreme weather and plant-disturbing organisms.